1982
DOI: 10.1007/bf00778510
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a mouse DNA fraction which encodes more informational than non informational RNA sequences

Abstract: A small fraction of single-stranded DNA (ssDNA), amounting to 1.5--2% of the total DNA, was isolated from native nuclear DNA of mouse Ascites tumour cells. In RNA-driven annealing reactions, 40--42% of the ssDNA, (labelled with [3H]-thymidine or 125I) could be hybridized to cytoplasmic RNA was compared with 4--4.5% for the non repetitious component of bulk DNA and 60--63% of the ssDNA could be hybridized to nuclear RNA as compared with 20--22% for bulk DNA. It was also found that most of the ssDNA sequences wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The finding that this complex is characterized by single-stranded DNA sequences is consistent with previous data showing that a minor fraction of the genomic DNA mainly derived from transcribed chromatin region, may be reproducibly isolated from purified DNA under the form of single-stranded DNA chains (ssDNA) (12,14,20,31). Further studies showed that ssDNA contains more informational than non informational sequences (32) and suDPorted the view that ssDNA arise via selective nucleasic breakaqe, probably at an early staqe of the DNA preparation procedure (12,16). However the possibility that limited DNA breakage occurs during cell life in relation with RNA synthesis cannot be excluded.…”
Section: I S C U S S I 0 Nsupporting
confidence: 90%
“…The finding that this complex is characterized by single-stranded DNA sequences is consistent with previous data showing that a minor fraction of the genomic DNA mainly derived from transcribed chromatin region, may be reproducibly isolated from purified DNA under the form of single-stranded DNA chains (ssDNA) (12,14,20,31). Further studies showed that ssDNA contains more informational than non informational sequences (32) and suDPorted the view that ssDNA arise via selective nucleasic breakaqe, probably at an early staqe of the DNA preparation procedure (12,16). However the possibility that limited DNA breakage occurs during cell life in relation with RNA synthesis cannot be excluded.…”
Section: I S C U S S I 0 Nsupporting
confidence: 90%
“…Besides, other ssDNA in nuclear DNA samples might interfere with isolation of the ssDNA transcripts. It was reported that ssDNA accounts for about 1% -2% of total nuclear DNA isolated from various eukaryotic cells [8]- [10], which was hypothesized to be generated by selective endogenous nuclease attacks at an early stage of the DNA purification procedure [10].…”
Section: Ideas For Further Experimental Test Of the Hypothesismentioning
confidence: 99%
“…Origin of RNA: (a) Rael cell line, Burkitt lymphoma (EBV + ); (b) Namalwa cell line, Burkitt lymphoma (EBV +); (c) HL60 cell line, acute promyelocytic leukemia; (d) BJAB cell line, Burkitt lymphoma (EBV -) (empty squares) and RD cell line, rhabdomyosarcoma (full squares); (e) uterine cervix carcinoma; (f) K562 cell line, acute myeloid leukemia; (g) uterine myoma; (h) chorioplacenta (4.5 month pregnancy); (i-j) T51 cell line normal lymphoblasts (EBV +) (crosses) and fetal liver (4.5 month pregnancy) (empty circles with a full core); (k) mouse L1210 leukemia (heterologous control). regions which encode mRNA sequences (Hanania et al, 1982).…”
Section: Characterization Of Ssdnamentioning
confidence: 99%
“…The lymphoid cells, either normal or malignant, in particular the Raji and Priess cells, exhibited similar multiplication rates for 2-3 days after the cell transfer, the cell density increasing from 2.5 x 105 cell/ml at time zero to 5-6 x 105 cell/ml, 1-1.2 x 106 cell/ml and 1.5-1.8 x 106 cell/ml after 24 h, 48 h and 72 h, respectively. All cell samples utilized for preparing DNA (Hanania et al, 1982).…”
Section: Cell Culturesmentioning
confidence: 99%